(3eTGQb GdCfhGQs - (3GdeLdSj, YHO Gddg Hf eMeO Jbjs
(3ChdgG (B:s
(3GdMeO ddg GdPj TQM UOhQ GdYdeGA GdQGSNjf HCNHGQ GdfHj(B... (3CeG HYO, ajbhd (B... (3Efj deG UQaJ HJhajb Gddg HQgI ef YeQj aj GdaMU Yf BKGQ Cgd GdHjJ (B...s
(3BNQgG (B:s
(3hJCcjOg HGdYWa KGfjG dQaY Jhge GdGcJaGA HGdZSd GdPj jPcQ CNjQG hGdChd CXgQ hEf cGf GdKGfj (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis